Characterization, Classification and Evaluation of Cultivated Soils under Different Toposequences in Pulwama District of Kashmir Valley - J.A. Wani and Masrat Maqbool, N.Z. Rehman, D. Ram (Journal of the Indian Society of Soil Science, 2017)
Knowledge about morphological, physical and chemical characteristics of soil is an essential requirement for successful crop establishment and output in an area. Taking this concept into cognizance, nine representative soil profiles were exposed in the study area and assessed for various properties. Results revealed that the soils developed in different topographies varied in their morphological properties. The soils showed varying degree of profile development from A-C, A-Bw-C to A-Bt-C horizons on foothills, low hill plateaus and inland valleys, respectively. The sand, silt and clay content were in the range of 11.7 to 60.6, 22.3 to 60.5 and 17.1 to 35.3%. Organic carbon (OC) ranged from 0.2 to 17.2 g kg-1 with a mean value of 4.2 g kg-1. Bulk density and particle density ranged from 1.21 to 1.58 Mg m-3 and 2.3 to 2.8 Mg m-3, respectively. The soils belonged to Entisol, Mollisol and Alfisol orders under taxonomical classification and II, III and IV classes under capability classification with limitations of slope, erosion and wetness. Proper soil managements and diversification of crops can decrease the risk of crop failures caused by such soil limitations.